2015
DOI: 10.1002/advs.201500117
|View full text |Cite
|
Sign up to set email alerts
|

Disorder Control in Crystalline GeSb2Te4 Using High Pressure

Abstract: disordered as possible. However, usually such chemical disorder is discouraged by the concomitant enthalpy rise, caused by the formation of homopolar bonds. Disorder can induce localization of electronic wavefunctions (e.g., Anderson localization [ 1 ] and thus can be crucial for the electronic properties of materials. [2][3][4][5][6][7] The current applications of phasechange materials (PCMs) take advantage of the fast transformations and large property contrast between the amorphous and the crystalline state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Upon fast crystallization of the glass, GST forms a metastable rocksalt phase, [34] in which Te atoms occupy one sublattice, while Ge, Sb, and vacancies occupy the second one in a random fashion. It has been shown experimentally [35][36][37] and theoretically [38][39][40] that the degree of disorder in rocksalt GST and similar compounds on the pseudobinary line can be tuned by thermal annealing or even pressure, so as to induce Anderson insulator-metal transitions induced by disorder.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Upon fast crystallization of the glass, GST forms a metastable rocksalt phase, [34] in which Te atoms occupy one sublattice, while Ge, Sb, and vacancies occupy the second one in a random fashion. It has been shown experimentally [35][36][37] and theoretically [38][39][40] that the degree of disorder in rocksalt GST and similar compounds on the pseudobinary line can be tuned by thermal annealing or even pressure, so as to induce Anderson insulator-metal transitions induced by disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, small fractions of antisite defects, yielding some Te–Te and Ge(Sb)–Ge(Sb) homopolar bonds, were found in recrystallized Ge 2 Sb 2 Te 5 obtained by DFT-based molecular dynamics (DFMD) simulations [79,80,81,82,83,84]. A thorough understanding of the effects of antisite defects on the localization properties is anticipated, nevertheless, in a recent study on pressuring rocksalt Ge 1 Sb 2 Te 4 at elevated temperatures, pairwise antisites were found but were shown to be ineffective for the localization properties of the occupied electronic states at the Fermi level [85]. To conclude, the presence and random distribution of a high amount of atomic vacancies in crystalline GST would unavoidably result in the formation of “vacancy clusters”, giving rise to the localization of electrons in crystalline GST.…”
Section: Discussionmentioning
confidence: 99%
“…It was predicted that the barrier of interlayer vacancy diffusion in GST crystals is not very high ~0.8–1.0 eV, and several such vacancy diffusion events were found in very short time scale ~50 picoseconds at 500 °C [17,42]. This transition barrier can be further reduced by pressure [85]. It is highly desirable to thoroughly test the vacancy ordering speed within the crystalline states in nanoscale phase change devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of disorder is tuned by increasing the annealing temperature. Recently, it has been shown that disorder in crystalline GST can also be tuned by pressure12. A disorder-driven MIT has been reported in GeTe nanowires as well13.…”
mentioning
confidence: 99%